2010
DOI: 10.1111/j.1467-9671.2010.01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Years of Research on Spatial Data Quality: Achievements, Failures, and Opportunities

Abstract: This article reflects on the past 30 years of academic research in the field of spatial data quality and tries to identify the main achievements, failures, and opportunities for future research. Most of this reflection results from a panel discussion that took place during the Sixth International Symposium on Spatial Data Quality (ISSDQ) in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 36 publications
2
81
0
1
Order By: Relevance
“…The disjunction of the uncertainty research with user requirement and practical application has now become one of the major problems which demands great emphasis (Devillers et al, 2010). The phenomena is partly generated by the deficiency of uncertainty research on the whole process from data acquisition and preparation, spatial analysis operation and results display from the perspective of certain application.…”
Section: The Research On Spatial Data and Spatial Analysis Uncertaintymentioning
confidence: 99%
See 3 more Smart Citations
“…The disjunction of the uncertainty research with user requirement and practical application has now become one of the major problems which demands great emphasis (Devillers et al, 2010). The phenomena is partly generated by the deficiency of uncertainty research on the whole process from data acquisition and preparation, spatial analysis operation and results display from the perspective of certain application.…”
Section: The Research On Spatial Data and Spatial Analysis Uncertaintymentioning
confidence: 99%
“…The early computer mapping exercise done at the Harvard Laboratory for Computer Graphics and Spatial Analysis in the late 1970s revealed that imperfection is inherent to spatial data and can directly influence the reliability of spatial analysis output (Chrisman, 2006). Works on the uncertainty of spatial data increased significantly with the arrival of GIS in the early 1980s with their capability to integrate spatial and non-spatial data, including the evaluation of specific data quality elements of vector, raster, and Digital Elevation Model (DEM) data, also remote sensing images (Devillers et al, 2010). Wu (2002) established a frame of GIS uncertainty and summarized the methods towards GIS data uncertainty.…”
Section: The Research On Spatial Data and Spatial Analysis Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations
“…They usually assume data is safe and not risky regardless of the intended usage context (Jones et al 2013). However, perceptions about the fitness-for-use of the data may diverge from untrained users, geo-IT experts and application domain experts (Grira et al, 2009;Devillers et al 2010). Accordingly, the assumption of safety usage of the data has led to a number of accidents and other adverse consequences that remind the need to protect users against the risks of data misuses (Larrivée et al, 2011).…”
Section: Risks Of Geospatial Data Missusementioning
confidence: 99%